2019
DOI: 10.1088/1742-6596/1286/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

The time in science: an interdisciplinary laboratorial approach

Abstract: In order to promote problem-based and active learning in the physics laboratory, we designed a flipped classroom focused on the Franck-Hertz experiment. The flipped classroom approach moves course content from the classroom to homework and uses class time for engaging activities and problem solving. This constructivist approach to teaching is an effective means of student-centred collaboration and it can promote active learning, enhance critical thinking and obtain the maximum use of student-faculty time toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Interdisciplinary learning paths are usually more effective because they can arouse greater interest and motivate students [1][2][3]. In educational research, both theoretical and empirical studies have extensively demonstrated the importance of the relationship between interest, motivation, and the learning process [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Interdisciplinary learning paths are usually more effective because they can arouse greater interest and motivate students [1][2][3]. In educational research, both theoretical and empirical studies have extensively demonstrated the importance of the relationship between interest, motivation, and the learning process [4][5].…”
Section: Introductionmentioning
confidence: 99%